STUDI PERBANDINGAN PROFESIONALISME MENGAJAR ANTARA GURU LAKI-LAKI DAN GURU PEREMPUAN DI SMK NEGERI 3 PEKANBARU - Hikmah Fazira; Hambali Hambali; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the development of teacher teaching condition at this time is quite show good achievement and quality. The quality of teaching of female teachers is no less good compared to male teachers. The problem formulation in this research is whether there is a difference of teaching professionalism between male and female teacher in SMK Negeri 3 Pekanbaru? This study aims to determine the difference between teaching professionalism between male and female teachers in SMK Negeri 3 Pekanbaru. The place of research conducted in SMK Negeri 3 Pekanbaru. The sample of this research is 13 male teachers and 13 female teachers as comparison in SMK Negeri 3 Pekanbaru. Technique of collecting data is done by using questionnaire and observation. This research method is descriptive quantitative. The results of the questionnaire showed that the professionalism of teaching male teachers is high with the percentage of 74.2 and the professionalism of teaching female teachers is high with percentage of 68%. Data were analyzed using homogeneity test and hypothesis test. Based on homogeneity test results obtained a statistical value of 0,000 with significant, because significant 1.909> 0.05 it can be seen that the homogeneity data. While the hypothesis test with different test analysis tools 2 separate samples are homogeneous showed obtained t_hitung equal to 1.839 with df 24 while t_tabel 1.71. Thus this proves there is a difference in teaching professionalism between male and female teacher in SMK Negeri 3 Pekanbaru. Thus t_count> t_table or 1,839> 1.71. So that sounds Ho rejected and that Ha sounds accepted, so the hypothesis in this study is accepted. Keywords: Professionalism, Male Teacher, Female Teacher